2020
DOI: 10.1108/jedt-10-2019-0268
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of using solar cells in regional electricity power supply of off-grid power systems in Iran

Abstract: Purpose Rural areas are one of the effective regions in economy and self-sufficiency field especially in agricultural and livestock section. Planning in the rural section and the effort in solving the problems of farmers lead to increase their interest in farming and manufacturing in the villages and decrease their migration to the cities and metropolitans. Therefore, the present study aimed at feasibility of electricity to a rural household in Iran using off-grid solar-based hybrid system. Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The most notable financial outputs of HOMER are total NPC and LCOE which represent the total Net Present Cost and the average cost of effective power production by the system per kWh. These parameters are calculated as follows (Abdali et al 2019 ; Jahangiri et al 2020b ). where is the total annual cost in $, CRF denotes the capital recovery factor, i shows the real interest rate in percent, R proj is the useful life of the project in years, and E served is the total electric load supplied in kWh/yr.…”
Section: Methodsmentioning
confidence: 99%
“…The most notable financial outputs of HOMER are total NPC and LCOE which represent the total Net Present Cost and the average cost of effective power production by the system per kWh. These parameters are calculated as follows (Abdali et al 2019 ; Jahangiri et al 2020b ). where is the total annual cost in $, CRF denotes the capital recovery factor, i shows the real interest rate in percent, R proj is the useful life of the project in years, and E served is the total electric load supplied in kWh/yr.…”
Section: Methodsmentioning
confidence: 99%
“…Using this approach, the electricity consumption of the village was estimated for 20 households. The estimated electricity consumption model for households and service centers, which is based on previous studies in Iran [43][44][45], is shown in Figure 2. According to this model, the average electricity consumption of households and service centers is 5.625 and 22.35 kWh/day, respectively.…”
Section: Estimation Of Electricity Consumptionmentioning
confidence: 99%
“…For the solar cells used in the present work, the lifetime is 20 years [48], the derating factor is 90% [49], the angle of the solar cells is equal to the latitude of the under study site [50], the orientation of the solar cells is to the south [51], and the ground reflection coefficient is 20% [52]. The cost of buying and replacing solar cells is $ 3200 and $ 3000 per kW, respectively [53].…”
Section: International Journal Of Photoenergymentioning
confidence: 99%